The Difficulties Encountered in Practice for the Field of Child and Adolescent Psychiatry After the Regulation on Assessment of Special Needs for Children (RASNC) - Sabide Duygu Uygun (Galenos Yayinevi, 2021)
Objectives:This study aimed to determine the challenges faced by child psychiatrists in our country during the assessment of special needs for children in practice after regulation on the assessment of special needs for children (RASNC) regulation.Materials and Methods:All specialists and academicians being the members of Turkish Association for Child and Adolescent Psychiatry were reached via e-mail between September and October 2020. A self-report questionnaire consisting of closed and open-ended questions about the variables of the individuals and processes for patients’ evaluation, diagnosis, referral to the health committee and report preparation after RASNC regulation was applied to volunteer participants.Results:The average age of the participants (n=156) was 33.8 (±4.1) years and 67.3% of them were female. In our study, it was shown that referrals to the committee were mostly made by a child psychiatrist, some psychiatric diagnoses were not educationally approved by the guidance research center (GRC), this might affect the diagnostic decision of the physicians, while evaluating the patients after RASNC, almost half of the participants had difficulties in at least one area of cognitive development, language, speech and communication and child psychiatry, and had problems related to border violation especially with different disciplines, the hospitals they worked in did not have a defined RASNC authorized physician, and patients with the same diagnosis in different centers might differ in terms of special needs area and level.Conclusion:In order to solve the difficulties faced by child and adolescent psychiatrists, rational arrangements should be made in RASNC regulation and then relevant physicians, hospital managers and GRC personnel should be trained on the regulation.